Le peuple et la coca. Populisme cocalero et restructuration de l’échiquier politique bolivien - Cécile Casen; Erwan Sommerer (Amnis)
The rise of the “Movimiento Al Socialismo” in the foreground of Bolivian political life in June, 2002 is the result of the progressive transformation of a social movement, from the promotion of purely sector-based interests – the defence of coca producers – to a logic of the privileged expression of the popular will: the gain of representativeness of the MAS has forced the extension of its mobilizing slogans. His leader, the former union activist Evo Morales, appears as the holder of a sovereignty which he claims to restore to the people so that it recovers a word stolen by the elites which shares the power since the democratic transition. This anti-authority and anti-imperialist speech carries the symbolic reorganization of a partisan scene from which are excluded the traditional parties, thrown outside the legitimate field of the real nation. So, between the respect for the Bolivian cultural variety and the defence of a people perceived as an opaque and homogeneous entity, the MAS is today at a point of uncertainty between populist withdrawal and renewal of the pluralistic game for the benefit of the demo-cratic institutions.